2018
DOI: 10.18585/inabj.v10i3.403
|View full text |Cite
|
Sign up to set email alerts
|

The dtxR Gene: A New Alternative Marker to Identify Corynebacterium ulcerans and Corynebacterium pseudotuberculosis by PCR Assay

Abstract: BACKGROUND: There are found some studies which reported the successfull of polymerase chain reaction (PCR) assay to identify Corynebacterium ulcerans and Corynebacterium pseudotuberculosis. This study aimed to describe the dtxR gene profile as a new marker for C. ulceran and C. pseudotuberculosis for the PCR assay.METHODS: Ten C. ulcerans and 35 C. pseudotuberculosis DNA sequences data registered in GeneBank was analyzed by bioinformatic tools. PCR primer was designed based on the concerved region and the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, the dtxR gene was used in this study, while the aforementioned researchers used the rpoB gene. Previously, we showed that the dtxR gene had some advantages over 16S rRNA and pld genes in identifying C. ulcerans and C. pseudotuberculosis (20). Moreover, we detected and identified three species of diphtheria-causing bacteria, while they only identified two (C. diphtheriae and C. ulcerans/C.…”
Section: Discussionmentioning
confidence: 90%
“…However, the dtxR gene was used in this study, while the aforementioned researchers used the rpoB gene. Previously, we showed that the dtxR gene had some advantages over 16S rRNA and pld genes in identifying C. ulcerans and C. pseudotuberculosis (20). Moreover, we detected and identified three species of diphtheria-causing bacteria, while they only identified two (C. diphtheriae and C. ulcerans/C.…”
Section: Discussionmentioning
confidence: 90%